(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study aims to analyze the contribution of religious values to the economic empowerment of students through entrepreneurship at the Fathul Ulum Islamic Boarding School in Jombang. The approach used is quantitative explanatory , with a population of all students involved in the Islamic boarding school’s entrepreneurial activities. The research sample was determined by proportional random sampling of 120 respondents. Data were collected through a Likert scale questionnaire and analyzed using the Partial Least Square – Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. The results of the study indicate that: (1) religious values have a positive and significant effect on the economic empowerment of students; (2) religious values have a positive effect on the entrepreneurial spirit of students; (3) entrepreneurship has a positive effect on improving the economic well-being of students; and (4) entrepreneurship acts as a significant mediating variable between religious values and the economic empowerment of students. These findings are in line with previous studies that emphasize the importance of integrating religious moral values in the formation of an entrepreneurial spirit and strengthening the community economy. Conceptually, this study enriches the Islamic entrepreneurship literature with the empirical context of Indonesian Islamic boarding schools. Practically, this research confirms the strategic role of Islamic boarding schools as educational institutions as well as centers for economic empowerment based on religious values and student entrepreneurship.